Research in Mathematics Education in Australasia 2012-2015 2016
DOI: 10.1007/978-981-10-1419-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Equity, Social Justice and Ethics in Mathematics Education

Abstract: The performativity policy mindset driving national and international testing highlights issues of equity in access and success according to socio-economic status, geographic location, ethnicity, gender and combinations of these factors. Researchers seek explanations for these inequities in terms encompassing engagement, participation and achievement to identify socially just and ethical practices at system, school and classroom level. The emergence of a theoretical perspective involving redistribution, recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…There is a need for caution that closed questions-presented as classroom tasks and/or assessment items-tell us only so much about students' knowledge and skills. Since students bring to their learning knowledge and understanding filtered through their social and cultural lenses (Vale et al 2016), it is only through exposing and seeking to understand the factors that influence them as they engage in financial problem-solving and decision-making that teachers can perhaps begin to address tensions between neoliberal and social justice ideologies noted earlier in this article in ways that are sensitive to local conditions, needs and interests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need for caution that closed questions-presented as classroom tasks and/or assessment items-tell us only so much about students' knowledge and skills. Since students bring to their learning knowledge and understanding filtered through their social and cultural lenses (Vale et al 2016), it is only through exposing and seeking to understand the factors that influence them as they engage in financial problem-solving and decision-making that teachers can perhaps begin to address tensions between neoliberal and social justice ideologies noted earlier in this article in ways that are sensitive to local conditions, needs and interests.…”
Section: Discussionmentioning
confidence: 99%
“…Students bring to their learning knowledge and understanding filtered through their social and cultural lenses (Vale et al 2016). Personal values-the convictions which one finds important (Seah 2016)-have also been found to influence students' responses to worded mathematical problems.…”
Section: Learning To Solve Real World Problemsmentioning
confidence: 99%
“…(iv) Recalibrate entry requirements Admissions to posts across all institutional levels (e.g., internships, studentships, and professorships) should be holistically reviewed, accounting for barriers that the applicant may have had to overcome 49 , adjusting pro-rata for career breaks, and considering the potential that they show beyond publications, impact factors, grade-point averages and standardised test scores.…”
Section: (Iii) Invest In Skills Training and Support For Edi Initiativesmentioning
confidence: 99%
“…According to previous research on fairness and social justice, public awareness of the disadvantages of students in remote rural environments and remote areas has gradually increased [14], [15]. Also, related research further found that compared with students in other urban areas, students in rural areas are less interested in learning science [16].…”
Section: Introductionmentioning
confidence: 99%